The International Classification of Functioning, Disability and Health-based factors related to physical activity level in adults with muscle diseases. Issue 2 (June 2019) - Ayvat, Fatma; Ayvat, Ender; Kilinç, Özge Onursal; Kilinç, Muhammed; Yildirim, Sibel Aksu
Abstract : The aim of this study was to investigate the physical activity (PA) level of adults with muscle diseases and the association of factors affecting PA behaviour. Forty-five adults with muscle diseases and 44 healthy participants were included. The PA was assessed by a SenseWear Armband and the International Physical Activity Questionnaire. The muscle strength, pain, fatigue severity, activity limitations, functional mobility level and quality of life were also assessed. Compared with the healthy group, adults with muscle diseases had significantly lower step counts and duration of moderate and vigorous PA ( P < 0.05). The BMI of the patients was related to total energy expenditure ( P < 0.05). The total number of steps, energy expenditure and duration of moderate PA of the patients were related to the 6-min walk test ( P < 0.05). There was a correlation between total, moderate and vigorous PA and mental health in adults with muscle diseases ( P < 0.05). The most important factors in reflecting PA in adults with muscle diseases are considered as BMI from personal factors, functional mobility from activity limitations and quality of life in the dimension of participation.